Theory and Practice of Academic Writing (Filologičeskij klass, 2015)
The paper presents the theory and practice of the academic essays's genre. The author introduces the notion, genre's history, its types and models, reveals the role in the modern world and the educational process. Particular attention is paid to the academic essay's genre features, structure and style. The article provides scientific community's recommendations on the preparation, writing and evaluation of the type of work. The tasks and questions is developed. It will allow the student to master the skill of questioning and understanding of oneself and others in culture and through culture, combining the knowledge of the subjective to the objective, the creation of texts on the subject studied, the correct participation in the «professional conversation», etc.